2018
DOI: 10.1002/ceat.201700638
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Crystal of Paracetamol and Trimethylglycine Prepared by a Supercritical CO2 Anti‐Solvent Process

Abstract: Paracetamol (PCA) and trimethylglycine (TMG) were co‐crystallized and micronized by means of the supercritical anti‐solvent (SAS) process to improve the tabletability of PCA. The effects of operating conditions on particle properties were investigated in detail. Characterizations were performed to confirm the co‐crystal state of PCA‐TMG. The results indicated that the same crystal form with different crystal habits was prepared. The optimal PCA‐TMG co‐crystals presented a much larger tensile strength, higher d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…As the continuous atomization of solution during injection, the semi-continuous SAS process often obtains co-crystals with small particle size. For example, paracetamol/trimethylglycine co-crystals < 10 μm were obtained by Zhao et al [ 31 ], which were much smaller than those obtained using the ball milling process. In the study of Cuadra et al [ 48 ], carbamazepine/saccharin co-crystals obtained using methanol as a solvent exhibited heterogeneous sizes with widths varying from 5 to 10 μm, while co-crystals obtained using ethanol and dichloromethane were much smaller.…”
Section: Applications Of Sas Process For Solid Multicomponent Systemsmentioning
confidence: 90%
See 1 more Smart Citation
“…As the continuous atomization of solution during injection, the semi-continuous SAS process often obtains co-crystals with small particle size. For example, paracetamol/trimethylglycine co-crystals < 10 μm were obtained by Zhao et al [ 31 ], which were much smaller than those obtained using the ball milling process. In the study of Cuadra et al [ 48 ], carbamazepine/saccharin co-crystals obtained using methanol as a solvent exhibited heterogeneous sizes with widths varying from 5 to 10 μm, while co-crystals obtained using ethanol and dichloromethane were much smaller.…”
Section: Applications Of Sas Process For Solid Multicomponent Systemsmentioning
confidence: 90%
“…By utilizing the tunable properties of scCO 2 at different operating conditions, SAS process offers the possibility to control the crystalline form of APIs in the micron, sub-micron and nano ranges, then to produce nanoparticles, microparticles, expanded hollow microparticles, micro/nano crystals, amorphous particles, and others [ 23 , 24 , 25 , 26 ]. In our previous studies, SAS process has been applied to produce 10-hydroxycamptothecin proliposomes [ 27 ], 10-hydroxycamptothecin/poly (L-lactic acid) microspheres [ 28 ], camptothecin microcrystals [ 29 ], gefitinib polymorphs [ 30 ], paracetamol/trimethylglycine co-crystals [ 31 ], nimesulide amorphous solid dispersions [ 32 ], and itraconazole solid dispersions [ 33 ]. These studies have demonstrated that SAS process holds great promise for the manipulation of the solid-state properties of APIs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic representation of a co-crystal structure, compared with a co-amorphous system and polymorph. Co-crystals are prepared by different methods, such as the supercritical anti-solvent (SAS) process [ 44 ], extrusion [ 45 ], freeze-drying [ 46 ], spray drying [ 47 ], and laser radiation [ 48 ]. However, chemical integrity is not always maintained with these preparation methodologies.…”
Section: Pharmaceutical Formulations Based On Structural Propertiesmentioning
confidence: 99%
“…Crystal engineering is an important way to achieve the assembly from molecules to materials on the basis of utilizing and controlling the intermolecular interactions. Cocrystals, as important parts of the research of crystal engineering, have been widely used in many fields such as energetic materials, nonlinear optics, ferroelectrics, and organic electronics. , In particular, the application of cocrystals in pharmaceuticals to improve physiochemical properties (such as bioavailability, stability, tabletability) of the active pharmaceutical ingredient (API) has drawn wide interest. From the perspective of supramolecular chemistry, a cocrystal is a kind of supramolecular structure assembled by intermolecular interactions (including hydrogen bonding, van der Waals force, π–π stacking, electrostatic interaction, etc. ). For strategic cocrystal preparation, it is critical to deeply understand the supramolecular synthons.…”
Section: Introductionmentioning
confidence: 99%